2004
DOI: 10.1021/jf030441c
|View full text |Cite
|
Sign up to set email alerts
|

Lower Fumonisin Mycotoxin Levels in the Grain of Bt Corn Grown in the United States in 2000−2002

Abstract: Fumonisins were monitored in corn grain collected from Bt hybrids grown in 107 locations across the United States in 2000-2002. Bt corn hybrids contain the Cry1Ab protein from Bacillus thuringiensis that controls European corn borers and other stalk-boring pests. Fumonisin levels were frequently lower in grain from Bt hybrids grown in field trials under conditions of natural (FACT trials) or manual insect infestation (university trials). Over three years of FACT trials, there were 126/210 comparisons when fumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(58 citation statements)
references
References 35 publications
2
53
0
3
Order By: Relevance
“…Some field trials, conducted in the USA in 2000-2002, demonstrated that fumonisin levels were frequently lower in grains of Bt hybrids than in non-Bt varieties (Hammond et al, 2004). Other experiments carried out in central Europe concluded that Bt maize hybrids slightly reduced the fusariotoxin level of maize (Magg et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Some field trials, conducted in the USA in 2000-2002, demonstrated that fumonisin levels were frequently lower in grains of Bt hybrids than in non-Bt varieties (Hammond et al, 2004). Other experiments carried out in central Europe concluded that Bt maize hybrids slightly reduced the fusariotoxin level of maize (Magg et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Within a year or two of the availability of fumonisin analytical standards, a field survey demonstrated that the incidence of the European corn borer increased Fusarium kernel rot and fumonisin concentrations (Lew et al 1991). Maize genotypes containing the anti-insectan Bt protein have reduced amounts of fumonisin compared to non-Bt genotypes (Bakan et al 2002;Hammond et al 2004;De La Campa et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The success of the Bt technology in maize (Armstrong et al 1995;Barry et al 2000), and cotton (Cattaneo et al 2006), is a strong rationale for the evaluation of this technology in sorghum as a means to combat specific target insect pests. Importantly, in addition to Bt's direct impact in impeding insect pest feeding damage, a secondary effect observed with the use of this technology is a significant reduction in accumulation of various mycotoxins in plant tissues (Abbas et al 2008;Bakan et al 2002;Hammond et al 2004). This secondary attribute of the Bt technology may serve as a valuable mechanism to limit quality issues of sorghum related to contamination of these toxins that may occur under certain conditions and fungal infestation levels (Ghali et al 2009;Reddy and Raghavender 2008;Reddy et al 2010).…”
Section: Target Input Traits For Sorghum Through Transformationmentioning
confidence: 99%